2016
DOI: 10.1039/c5cp03139g
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic etching of monolayer graphene at low temperature via carbon oxidation

Abstract: In this work, an easy method to etch monolayer graphene is shown by catalytic oxidation in the presence of ZnO nanoparticles (NPs). The catalytic etching of monolayer graphene, which was transferred to the channel of field-effect transistors (FETs), was performed at low temperature by heating the FETs several times under an inert gas atmosphere (ZnO + C → Zn + CO or CO2). As the etching process proceeded, diverse etched structures in the shape of nano-channels and pits were observed under microscopic observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 54 publications
(101 reference statements)
0
16
0
2
Order By: Relevance
“…26,35 Inheriting the advantages of carbons from both ZIF-67 and ZIF-8, the BMZIF layer was converted into N-doped porous carbon with high graphitization. The PAN core was turned into carbon that can be etched by ZnO from the decomposition product of Zn(Ac) 2 in the composite fiber core, 36,37 as shown in Figure 1C, according to the carbothermal reduction ZnO + C / Zn + CO 2 or CO. The carbon core can be completely etched out by increasing the content of Zn(Ac) 2 .…”
Section: Resultsmentioning
confidence: 99%
“…26,35 Inheriting the advantages of carbons from both ZIF-67 and ZIF-8, the BMZIF layer was converted into N-doped porous carbon with high graphitization. The PAN core was turned into carbon that can be etched by ZnO from the decomposition product of Zn(Ac) 2 in the composite fiber core, 36,37 as shown in Figure 1C, according to the carbothermal reduction ZnO + C / Zn + CO 2 or CO. The carbon core can be completely etched out by increasing the content of Zn(Ac) 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The profile heights and the atomically resolved structures prove that only the top EG layer has been etched. The formation mechanism of nano-trenches on EG layers is complex, but the most possible reason may also be related to oxidation of carbon atoms, and metal particles can be activated to move forward and scissor graphene sheets gradually at elevated temperatures [17,18]. Oxygen may be released from the chamber or the sample surface, and only a very small amount is contained.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of catalysict etching has been discussed accordingly through experiments, and further demonstrated by computational simulations [15,16]. Along with hydrogenation or oxidation of carbon atoms in H 2 or O 2 gas environments, metal particles can be activated as catalysts to move forward and scissor graphene sheets gradually at elevated temperatures [17,18]. As a result, graphene patterns with different shapes can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Previous studies have shown that under certain conditions nanoparticles can interact with graphene and, in some cases, they can induce defects or even etch the graphene layer. [15][16][17] For example, an etching process has been utilised for graphene cutting to create nanoribbons. [16] One of the importantc haracteristics of graphene is that it can serve as ao ne-atom-thickm embrane.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] For example, an etching process has been utilised for graphene cutting to create nanoribbons. [16] One of the importantc haracteristics of graphene is that it can serve as ao ne-atom-thickm embrane. Due to their oneatom thickness andm echanical, thermal, and chemical robustness, graphene membranes with nanoscale pores are expected to enable extremelyh igh efficiencyi nv arious applications such as DNA translocation, selectives eparation of ions and chemicals pecies, and water desalination.…”
Section: Introductionmentioning
confidence: 99%